Managing sports experiences in the context of tourism - Marko Peric (UTMS Journal of Economics, 2015)
Participation in sports activities combined with unique sports resources can provide people with extraordinary experiences. It is especially true for tourism where sports activities are an important content of stay. The aim of this paper is to analyse how sports experiences could be planned and managed for the tourism purposes from the aspect of sports facility managers. In addition, the interrelations within the four realms of an experience were analysed and supported by proposed management models and examples. Results of the analysis indicate that it is possible for a facility to provide a full spectrum of experiences but only if it meets the standards of professional sports. Recommendations suggested by the paper provide new insight on organising the sports offer in the destination, and can be used by sports facility managers in order to better serve sports and sports tourism needs.
Keywords: L83; 330; tourism; sport; experience; management models